The Relationship Between Mother's Knowledge And The Completeness Of Basic Immunization At Tenga Public Health Center - Wongkar, Carla; Alfitri, Rosyidah (Universitas Prima Indonesia, 2025)
The immunization program is a form of basic health efforts in an effort to accelerate breaking the chain of transmission of PD3I (Immunization-Preventable Diseases). Factors related to the completeness of immunization are very important to understand as one of the efforts to increase the coverage rate of basic immunization completeness. The purpose of this study was to determine the relationship between maternal knowledge about basic immunization and the completeness of basic immunization in the Tenga Community Health Center Work Area. The study used a cross-sectional approach. Samples were taken by purposive sampling totaling 70 respondents. Data analysis using chi square in the SPSS V.25 computer program. The analysis results showed no relationship between knowledge and the completeness of basic immunization (p = 0.001). Based on the results of this study, it can be concluded that the completeness of basic immunization is not influenced by maternal knowledge about basic immunization.